Resveratrol, novel application by preconditioning to attenuate myocardial ischemia/reperfusion injury in mice through regulate AMPK pathway and autophagy level. Issue 15 (5th July 2022) - Li, Haiyan; Zheng, Fuchun; Zhang, Yanmei; Sun, Jiajia; Gao, Fenfei; Shi, Ganggang
Abstract: Myocardial ischemia/reperfusion injury (MI/RI) is the main cause of deaths in the worldwide, leading to severe cardiac dysfunction. Resveratrol (RSV) is a polyphenol plant‐derived compound. Our study aimed to elucidate the underlying molecular mechanism of preconditioning RSV in protecting against MI/RI. Mice were ligated and re‐perfused by the left anterior descending branch with or without RSV (30 mg/kg·ip) for 7 days. Firstly, we found that RSV pretreatment significantly alleviated myocardial infarct size, improved cardiac function and decreased oxidative stress. Furthermore, RSV activated p‐AMPK and SIRT1, ameliorated inflammation including the level of TNF‐α and IL‐1β, and promoting autophagy level. Moreover, neonatal rat ventricular myocytes (NRVMs) and H9c2 cells with knockdown the expression of AMPK, SIRT1 or FOXO1 were used to uncover the underlying molecular mechanism for the cardio‐protection of RSV. In NRVMs, RSV increased cellular viability, decreased LDH release and reduced oxidative stress. Importantly, Compound C(CpC) and EX527 reversed the effect of RSV against MI/RI in vivo and in vitro and counteracted the autophagy level induced by RSV. Together, our study indicated that RSV could alleviate oxidative stress in cardiomyocytes through activating AMPK/SIRT1‐FOXO1 signallingpathway and enhanced autophagy level, thus presenting high potential protection on MI/RI.